1999
DOI: 10.1104/pp.121.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Flavan-Containing Cells Delimit Frankia-Infected Compartments in Casuarina glauca Nodules

Abstract: We investigated the involvement of polyphenols in the Casuarina glauca-Frankia symbiosis. Histological analysis revealed a cellspecific accumulation of phenolics in C. glauca nodule lobes, creating a compartmentation in the cortex. Histochemical and biochemical analyses indicated that these phenolic compounds belong to the flavan class of flavonoids. We show that the same compounds were synthesized in nodules and uninfected roots. However, the amount of each flavan was dramatically increased in nodules compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 47 publications
(4 reference statements)
4
30
0
Order By: Relevance
“…More recently, a second level of compartmentalization was described in Casuarina glauca nodules based on accumulation of flavans, which occurs in uninfected cells in the endodermis and cortex. These cells form layers that delimit Frankia-infected compartments in the nodule lobe and may play a role in restricting bacterial infection to certain zones of the nodule (Laplaze et al 1999). …”
Section: Nodule Development and Functioningmentioning
confidence: 98%
“…More recently, a second level of compartmentalization was described in Casuarina glauca nodules based on accumulation of flavans, which occurs in uninfected cells in the endodermis and cortex. These cells form layers that delimit Frankia-infected compartments in the nodule lobe and may play a role in restricting bacterial infection to certain zones of the nodule (Laplaze et al 1999). …”
Section: Nodule Development and Functioningmentioning
confidence: 98%
“…The use of in situ hybridization established that chalcone synthase transcripts accumulate in flavan containing cells at the apex of the nodule lobe. Laplaze et al 79 hypothesized that cell specific flavan biosynthesis and accumulation delimit cortical compartments containing Frankia-infected cells and might restrict endophyte invasion. The meaning of this compartmentation is not understood, but obviously some signal exchange with the endophyte is needed for its development.…”
Section: Flavonoids and Arbuscular Mycorrhizamentioning
confidence: 99%
“…The involvement of polyphenols in the Casuarina glauca-Frankia symbiosis was investigated. 79 Histological analysis revealed a cell specific accumulation of phenolics in C. glauca nodule lobes, creating a compartmentation in the nodule cortex. Histochemical and biochemical analyses indicated that these phenolic compounds belong to the flavan class of flavonoids.…”
Section: Flavonoids and Arbuscular Mycorrhizamentioning
confidence: 99%
“…Kaempferol and quercetin, along with other phenolic compounds, were the dominant flavonoids in the tested Casuarina species in Egypt (Saleh and El-Lakany 1979). Phenolic compounds may also limit Frankia colonization compartments inside the host nodule tissues (Laplaze et al 2000). The added quercetin increased the isolated Frankia colonies, while fungal contaminants were reduced, in the isolation medium (Sayed and Wheeler 1999).…”
Section: Age Of Plant and Direct Interaction With Littermentioning
confidence: 98%